ESTIMASI FUNGSI PRODUKSI DAN EFISIENSI ALOKASI SUMBERDAYA PETANI KEDELAI DI LOMBOK BARAT - Nufus, Nurhayatin (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
This research aims to analyses factors influence on production and resources allocation of soybeans by farmer at West Lombok. Production function was estimated from survey data and technical efficiency was used to indicate farm management level through maximum likelihood, which was transformed into frontier stochastic production function. The land size, fertilizer (urea and TSP), labor and pesticide influence the production of soybean at site. The technical efficciency level of Soybean fann was 95,6 percent The usage of TSP and pesticide reached allocative efficiency while urea and seeds were al/ocative efficiency yet